+0  
 
0
204
1
avatar

Please help! I'm confused on this! Please show work. Thank you!!

 Sep 25, 2018
 #1
avatar+111329 
+1

h(t)    =-3t^2  + 12t + 60

 

Let h(t)  = y

 

We want the form

 

y  = a (x - h)^2  + k      where k  will give us the max  height

 

Factor out the  -3

 

y  = -3 (t^2 - 4t - 20)          take 1/2 of 4  = 2...square it = 4 ...  add and subtract this within the parentheses

 

y = -3 ( t^2  - 4t + 4  - 20  - 4)  simplify within the parenthese

 

y = -3 (t^2 - 4t + 4   - 24)      factor the first three terms

 

y = -3 [ (t - 2)^2  - 24 ]     distribute the "-3"  across the terms in the bracket

 

y = -3 (t - 2)^2  + 72

 

k = 72  =  max ht  (in feet)

 

 

cool cool cool

 Sep 25, 2018

14 Online Users